mosby's color atlas of infectious diseases consult - Falagas, Matthew E..; Mylonakis, Eleftherios; Gorbach, Sherwood L., 1934- (health science, 2000)
"Using the two-page, templated organization of the 5-Minute Consult series, Gorbach's 5-Minute Infectious Diseases Consult, Second Edition provides comprehensive coverage for clinicians dealing with infectious diseases. The two major sections of the book cover chief complaints and individual diseases and disorders. Additional materials include summary information about individual microorganisms as well as numerous elements related to drugs for infectious disorders. A team of international authorities provides actionable information, supported by current research and practice guidelines.Features Include: Comprehensive coverage of infectious diseases, important symptoms, microorganisms, and anti-infective drugs Coverage of emerging infectious diseases such as H1N1 flu Increased coverage of tropical diseases Two-page, tightly written chapters Updated information about management of HIV/AIDS "--Provided by publisher.
Rev. ed. of: 5-minute infectious diseases consult / editors, Sherwood L. Gorbach, Matthew Falagas ; associate editors, Eleftherios Mylonakis, David R. Stone. c2001.
Includes bibliographical references and index.
Keywords: Communicable Diseases -- Handbooks